Un dispositif d’accompagnement « multisitué » : repenser les parcours d’accompagnement des jeunes Nigérianes en Italie - Rosanna Cima; Maria Livia Alga (Sociétés et Jeunesses en Difficulté)
This contribution focuses on the processes and results of a research-action carried out on the psychosocial care of young Nigerian migrant women in Verona, in the north-east of Italy, between 2011 and 2016. This research, which involved health professionals, social workers and cultural mediators, aimed to develop new practices and tools in the face of the constant failure of the institutions, especially in dealing with young Nigerian prostitutes, victims of trafficking. Indeed, the majority of these women who applied to social services suffered institutional ------ mapping tools, it has been possible to investigate the institutional geographies involved in the care of young Nigerian users. The emergence of the importance of informal care places has changed the networks of this care thanks to the figure of the expert user. A new device, called “multi-located”, was therefore experimented.